2017
DOI: 10.4054/demres.2017.36.9
|View full text |Cite
|
Sign up to set email alerts
|

Age norms, family relationships, and home leaving in Italy

Abstract: BACKGROUNDPrevious research has shown that social norms have an influence on young adults' life course transitions. However, few studies have explicitly and directly tested the idea that perceived age norms affect the decision to leave the parental home. OBJECTIVEI ask whether normative factors are correlated with the decision to leave the family nest in Italy, and whether this association depends on a system of perceived costs and benefits, parental approval of their children's decisions, and the quality of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
1
22
0
6
Order By: Relevance
“…First, our sample mean age was 17.74 years old. Given that the mean age of leaving home in urban areas of Turkey is 23.3 years old (Koç 2007), adolescents may consider the year after high school graduation as too early to move out and they may adhere to the age norms for leaving home (Tosi 2017). Thus, with an older sample we may find a higher percentage of motivated individuals.…”
Section: Motivation To Leave Home After High Schoolmentioning
confidence: 99%
“…First, our sample mean age was 17.74 years old. Given that the mean age of leaving home in urban areas of Turkey is 23.3 years old (Koç 2007), adolescents may consider the year after high school graduation as too early to move out and they may adhere to the age norms for leaving home (Tosi 2017). Thus, with an older sample we may find a higher percentage of motivated individuals.…”
Section: Motivation To Leave Home After High Schoolmentioning
confidence: 99%
“…The role of parents is apparent in contexts with the custom of arranged marriage where parents themselves play a dominant role in contracting the marriages of their children. However, parents play an important role in children's marriage even in contexts with considerable youthful autonomy, such as Italy and the United States (Thornton et al, 2008; Tosi, ). Parents' attitudes likely influence children's marriage in a variety of ways.…”
Section: Conceptualizationmentioning
confidence: 99%
“…Others used panel data to more rigorously assess the influence of timing attitudes. Most notably, Tosi () found that age norms influence when young people in Italy leave their parental home as a result of marriage or other reasons. Specifically, young Italians living with their parents who thought they were too young to leave home were more likely to still be living with their parents 4 years later, rather than having left home for marriage or other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in recent years in the study of transitions in young people and the adaptation of their normative expectations to the structural determinants of the socio-economic environment [50]. Numerous frameworks for interpretation have sought to analyse the youth condition through the lens of the concept of transition.…”
Section: Towards a Plural Theoretical Model That Integrates Generatiomentioning
confidence: 99%